1994
DOI: 10.1046/j.1365-313x.1994.6010021.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of protein domain function encoded by the myb‐homologous maize genes C1, Zm 1 and Zm 38

Abstract: SummaryTwo maize genes, Zm I and Zm 38, related to the regulatory anthocyanin gene CI were analyzed molecularly and used for fusion constructs in transient domain swapping experiments with the C1 wild-type gene. It was shown that both genes (Zm 1 and Zm 38) influence the expression of the A 1 locus, a target gene for C1. Zm I activates the A1 promoter, however it does not turn on the whole anthocyenin pathway. The Zm 38 gene product shows functions similar to C1-1, a dominant inhibitor of the Clwild-type gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…An analogy for this may be the IN1 protein, which has sequence similarity to MYC class transcription activators and down-regulates many of the structural genes of the anthocyanin pathway (28). Additionally, the MYB class gene zm38 has been shown to inhibit transcription activation of the a1 promoter by C1͞R1 in transient expression assays (29). We are designing and conducting gene expression studies to attempt to distinguish among these possible models.…”
Section: Discussionmentioning
confidence: 99%
“…An analogy for this may be the IN1 protein, which has sequence similarity to MYC class transcription activators and down-regulates many of the structural genes of the anthocyanin pathway (28). Additionally, the MYB class gene zm38 has been shown to inhibit transcription activation of the a1 promoter by C1͞R1 in transient expression assays (29). We are designing and conducting gene expression studies to attempt to distinguish among these possible models.…”
Section: Discussionmentioning
confidence: 99%
“…Maize c1 is part of a gene family which includes pl (purple) , p (pericarp) (Grotewold et al, 1991), zm1 (Zea mays1) (Franken et al, 1994), and zm38 (Zea mays38) (Franken et al, 1994), all of which are involved in regulation of branches of the phenylpropanoid pathway. demonstrated that pl has a duplicate function to c1 but differs in its tissue specificity.…”
Section: Introductionmentioning
confidence: 99%
“…They have only been partially characterized to date but they also appear to be involved in regulation of the anthocyanin pathway (Franken et al 1994). In vitro, Zm38 can act as a repressor that inhibits production of anthocyanin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a transcription factor has already been numbered, every possible effort should be made to consider that number as part of the new name, e.g. maize Zm38 (Franken et al, 1994) should become ZmMYB38. Since it is realized that many transcription factors are known by their genetic names, this nomenclature will permit the use of various different synonyms.…”
mentioning
confidence: 99%